Rayney's tax planning for family and owner-managed companies 2021/22 - Rayney, Peter (London, England : Zed Books, 2021)
"Widely recognised as the leading title targeted at privately owned companies and their advisors. It provides high quality advice on a range of factors impacting the tax planning activity undertaken by most businesses. The book is written by Peter Rayney, the current President of the CIOT. His experience in providing advice and solutions to companies of all sizes is reflected in this updated content. The structure of the book enables reader to navigate quickly to an area of that interests them, whether it be the extraction of funds from the company, remuneration strategies or the treatment of benefits and expenses. All chapters contain practical worked examples to back up the guidance given. The 2021/22 edition is updated in line with Finance Act 2021 and related HMRC guidance as well as any relevant new case summaries. The previous edition contained extensive new content on the COVID-19 support measures and this is also be updated and extended."--
1 The Family and Owner-Managed Company, Tax Planning Concepts, and Tax Avoidance -- 2.Extracting Funds from the Company -- 3.Shareholding and Corporate Structures -- 4.Trading Company and Investment Company Computations under CTSA -- 5.Remuneration Strategies -- 6.Personal Service Companies and Off-Payroll Working -- 7.Benefits and Expenses -- 8.Providing shares to employees -- 9.Distribution of profits and dividend planning -- 10.Pension Scheme Strategies -- 11.Share Issues and Financing the Company's Activities -- 12.Expanding the Company's Activities and Structuring Business Acquisitions -- 13.Share Transfers, Share Buy-Backs and Company Reorganisations/Demergers -- 14.Valuing a Family or Owner-Managed Company -- 15.Selling the Owner-Managed Business or Company -- 16.Winding-Up, Administration of Companies and Disincorporation -- 17.Succession Planning and Passing on the Family or Owner-Managed Company
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Tax planning -- Great Britain; Family-owned business enterprises -- Taxation -- Great Britain; Family-owned business enterprises -- Taxation; Taxation,Corporate tax; Electronic books